Liaison amid problem behavior and traumatic dental injury among children aged 12-15 years in Bhopal - Naveen S Yadav; Vrinda Saxena; Manish Jain; Kapil Paiwal (Wolters Kluwer Medknow Publications, 2015)
Introduction: Liaison amid problem behavior and traumatic dental injury among children aged 13-15 years are consequential due to multifactorial dental, orofacial skeletal, psycosocial behavior pattern. The probable etiology is been equated overjet; inadequate lip coverage is the major etiological factors accountable for traumatic dental injuries. Aims: The aim was to assess the relationship of problem behavior, type of lip coverage, and the size of overjet with the traumatic dental injury among children aged 12-15 years. Materials and Methods: A cross-sectional study was conducted among 200 children aged 12-15 years in Bhopal, India. Data were collected through clinical examinations in children and interviews with parents. Traumatic injuries were recorded according to Garcia-Goday's classification. The informant - rated version of the strengths and difficulties questionnaire was used to identify problems behavior. Results: About 16.4% subjects had more than 5 mm overjet, and 20.4% subjects had inadequate lip coverage. The largest number of injuries were presented by 15-year-old children (43.90%) followed by 14 and 13 years old children. The traumatic dental injury showed 6.8% association with problem behavior, age, sex, type of lip coverage, and the size of overjet. Conclusion: Problem behavior along with the type of lip coverage and the size of overjet plays a role in the occurrence of traumatic dental injury.